2021
DOI: 10.1021/acsami.1c13447
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and Permeating Modification Effect of n-type Non-fullerene Acceptors toward High-Performance Perovskite Solar Cells

Abstract: Interface passivation in the electron transport layer (ETL) has emerged as a very important and challenging topic for the improvement of stability and efficiency of perovskite solar cells (PSCs). Here, we introduce the n-type small organic molecule Y6 that acts as an effective ETL modifier through surface engineering. As a result, the simple PCBM + Y6 ETL led to significantly stronger light absorption, higher electron extraction ability and transportability, and reduced recombination loss in regular MAPbI 3 PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The laboratory certified efficiency of PSK single junction cells has increased from 3.8% [97] in 2009 to 25.5% [50,98] currently, making it an ideal top-cell for TSC due to its bandgap tunability [99][100][101], high defect tolerance [102,103], high absorption coefficient [104], and steep absorption edge [105][106][107]. The current study found that mirror-like PSK cells exhibit superior PV performance [108][109][110][111], contrary to the robust light trapping of pyramid-textured Si [112,113]. To evaluate the effects of textured PSK interfaces on the light absorption, Xu et al [114], utilized polystyrene spheres masked on the hole transport layer (HTL, 50 nm) to increase the roughness and reduce the reflection loss at the incident side.…”
Section: Single Junction Solar Cellmentioning
confidence: 65%
“…The laboratory certified efficiency of PSK single junction cells has increased from 3.8% [97] in 2009 to 25.5% [50,98] currently, making it an ideal top-cell for TSC due to its bandgap tunability [99][100][101], high defect tolerance [102,103], high absorption coefficient [104], and steep absorption edge [105][106][107]. The current study found that mirror-like PSK cells exhibit superior PV performance [108][109][110][111], contrary to the robust light trapping of pyramid-textured Si [112,113]. To evaluate the effects of textured PSK interfaces on the light absorption, Xu et al [114], utilized polystyrene spheres masked on the hole transport layer (HTL, 50 nm) to increase the roughness and reduce the reflection loss at the incident side.…”
Section: Single Junction Solar Cellmentioning
confidence: 65%
“…For the case of the single junction and without any special optical structure, many literature studies [110][111][112][113][114] have reported that the better the mirror-like effect of the PSK, the better the electrical performance of the device. Since the light absorption capability of planar PSK is mainly determined by the bandgap, the improvement of PCE with the same bandgap basically depends on the electrical gain.…”
Section: Experimental Optimization Of Electrical Propertiesmentioning
confidence: 99%
“…[3][4][5][6][7][8] A more recent key development to improve the efficiency and the stability of perovskite solar cells is the usage of passivating additives to reduce the number of defect states in the perovskite grain boundaries or at its interface to the charge extraction layers. This is either achieved by introducing passivating layers below and on top of the perovskite layer, [9][10][11][12][13][14] or by mixing different types of additives into the precursor solution. [15][16][17][18][19][20][21] The advantage of the latter approach is that the passivating effect is not limited to the interface, but also improves the perovskite grain boundary properties.…”
Section: Introductionmentioning
confidence: 99%